1968
DOI: 10.1172/jci105729
|View full text |Cite
|
Sign up to set email alerts
|

Surface tension, metabolic activity, and lipid composition of alveolar cells in washings from normal dog lungs and after pulmonary artery ligation

Abstract: A B S T R A C T Lung-washings from mammalian species are a rich source of surfactant and of cells, predominantly alveolar macrophages, that could be important in the metabolism of the surfactant. We obtained washings from normal dogs, and from dogs that had had one pulmonary artery (PA) ligated 1 or 2 days earlier. Centrifugation of wash (400 x g for 20 min) separated a sediment, made up of cells at the bottom and a white layer, largely acellular, from the supernatant. The volume of sediment averaged 2.1 + 1.4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

1969
1969
2007
2007

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…This is significantly higher than the mean concentration of phospholipids in BAL fluid from guinea pig (2·65 mg g − 1 ) [33] and lambs (2·5 mg g − 1 ) [31]. In addition, the analysis of lipid composition of lung washings and BAL fluid of dog lung showed the presence of a 'white layer' with a very high content of phospholipids (501·4 mg g − 1 ), which was not described in other species [35]. Based on these considerations we suggest that high LLMI in dogs may be explained by a high concentration of phospholipids in dog lung.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…This is significantly higher than the mean concentration of phospholipids in BAL fluid from guinea pig (2·65 mg g − 1 ) [33] and lambs (2·5 mg g − 1 ) [31]. In addition, the analysis of lipid composition of lung washings and BAL fluid of dog lung showed the presence of a 'white layer' with a very high content of phospholipids (501·4 mg g − 1 ), which was not described in other species [35]. Based on these considerations we suggest that high LLMI in dogs may be explained by a high concentration of phospholipids in dog lung.…”
Section: Discussionmentioning
confidence: 60%
“…[34] quantified the mean concentration of phospholipids in BAL fluid obtained from the dog lung as 15·4 mg g − 1 of lung weight. In addition, the analysis of lipid composition of lung washings and BAL fluid of dog lung showed the presence of a 'white layer' with a very high content of phospholipids (501·4 mg g − 1 ), which was not described in other species [35]. In addition, the analysis of lipid composition of lung washings and BAL fluid of dog lung showed the presence of a 'white layer' with a very high content of phospholipids (501·4 mg g − 1 ), which was not described in other species [35].…”
Section: Discussionmentioning
confidence: 73%
“…In the present investigation large number of mitochondria was encountered in camel type-II pneumonocyte . Tyler and Pearse, (1965), Said , Kiein, Norell andMaddox, (1966) and Said, Harlan, Burk and Elliot (1968) , have pointed out that the huge number of mitochondria reflect a high level of oxidative metabolic activity in their cytoplasm; moreover the glycolytic and the hexose monophosphate pathway enzymes may be another important source of energy and may play a role in the synthesis of pulmonary phospholipids and fatty acids. According to Hoffman (1972), Gill andReiss(1973) and Kuhn (1978) the osmiophilic inclusions were considered as a storage form of surfactant due to their high content of phospholipids mainly dipalmitoyl phosphatidycholine; in this respect Clements and King (1976), Collet and Chevalier (1977), Meyrick and Reid (1977), Weibel and Gil (1977 and Junqueira and Carneiro (1983), demonstrated that the osmiophilic lamellar bodies contain a concenterate of the disaturated phospholipid dipalmitoyl lecithin; the same material that has been isolated from the alveolar surface lining.…”
Section: Discussionmentioning
confidence: 99%
“…a potentially avoidable hazard, has been shown to be closely correlated with the severity and prognosis of the IRDS (14, 16). If birth asphyxia has a similar adverse effect on the Qpc eff in preterm infants as it does in normal term infants then this may be of considerable importance in the development of the IRDS, as it has been shown experimentally that pulmonary hypoperfusion can cause surfactant deficiency (15) and low effective pulmonary capillary blood flows have been found in preterm infants with the IRDS (2, 12).…”
Section: Discussionmentioning
confidence: 99%